Polimorfismo S19W (Ser19Ter) de la APOA5 y su relación con la hipertrigliceridemia en una población de Colombia (2017)
Introduction: Cardiovascular diseases (CVD) are responsible for 29.69% of the deaths in Colombia. Several studies have shown that hypertriglyceridemia is an independent risk factor for CVD. ApoA5 gene S19W (Ser19Ter) polymorphism has been associated with hypertriglyceridemia in some populations; however, their influence in Colombia is unknown. Objective: To determine the relationship between S19W polymorphism and hypertriglyceridemia in Colombian population. Methodology: Transversal crossover Studio, included a total of 400 individuals. TAG was quantified and genotyped using the technique SnapShot and mini sequencing. The results were analyzed using genetic analysis software Arlequin 3.5.1.2. Results: S19W (Ser19Ter) polymorphism showed three profiles, CC, GG and CG. The S19W polymorphism was characterized both affected and not affected. There wasn ́t significant differences in the distribution when the two groups are compared. Discussion: Various mechanisms have been proposed to support hypertriglyceridemia as a risk factor for CVD, including the APOA5 counted. The study found that the study population is in Hardy Weinberg and CC genotype as the most frequent. The GG and GC genotypes showed significant values in the group of affected subjects (p = 0.002 and 0.03). It demonstrated the existence of a close relationship between the Ser19Trp polymorphism and hypertriglyceridemia (p<0,01). Conclusion: It was possible to demonstrate the existence of a relationship between polymorphism Ser19Trp of ApoA5 with elevated levels of TAG (p<0,01)